CMOK to YOu To: A Correspondence - Živančević, Nina (punctum books, 2016)
CMOK to YOu To presents the 2015 email correspondence of the Serbian-born poet, art critic and playwright Nina Živančević and Canadian cultural theorist Marc James Léger. In December of 2014 Léger invited Živančević to contribute a text to the second volume of the book he was editing, The Idea of the Avant Garde - And What It Means Today. Taken with each other's idiosyncrasies, their correspondence gradually shifted from amiable professional exchanges and the eventual failure to organize a scholarly event to that of collaborating on some kind of writing project. Several titles were attempted for the eventual book - Marshmallow Muse: The Exact and Irreverent Letters of MJL and NZ, The Orange Jelly Bean, or, I Already Am Eating from the Trash Can All the Time: The Name of This Trash Can Is Ideology, The Secreted Correspondence of Mme Chatelet and Voltaire, and I'm Taken: The E-Pistolary Poetry of Kit le Minx and Cad - but none of these proved to be more telling than CMOK, the Serbian word for kiss, which sums up the authors' quest for "harmony" in an altogether imperfect world and literary medium. In this book, names of real people were changed in order to protect those who might otherwise be offended by the unguarded and absurdist commentary of its authors. Despite this fact, it is the fragility and elasticity of the writers' superegos that is tested as they vacillate from personal registers to intellectual strata. At once a cis-avant-gardist's exploration of anti-art and a poet's claim to some weak form of autonomy, CMOK delights in both the pleasures of casual email and the sublime realizations of Jacques Lacan's theory of sexuation. CMOK is a hybrid genre and a quest into the real of virtuality that defies the literary standards. Its authors, who never met, answer one another's basic needs and questions, separated as they are by time zones and the ocean, but not culturally or spiritually.